Penerapan Penyajian Laporan Keuangan Berdasarkan PSAK 1 Dan Tata Kelola Yang Baik Pada Perusahaan Ades - Lira Fadia Rahma (Universitas 17 Agustus 1945, 2023)
Presentation of financial statements is an accounting standard that will explain the components of a financial report, fair presentation, as well as the fundamental accounting concepts, disclosure policies, as well as the structure and content of financial reports. The characteristics in the presentation of financial statements are fair presentation and compliance with PSAK, maintaining business, accrual basis, materiality and aggregation, offsetting, frequency of reporting, comparative information, and presentation consistency. There are several components of the financial statements presented, namely the statement of financial position, income statement, cash flow statement, statement of changes in equity, and notes to the financial statements. Corporate governance is a company's internal control system whose main objective is to manage significant risks to fulfil its business objectives through safeguarding company assets and increasing shareholder investment value in the long term. A company must also apply the principles of corporate governance, there are five principles that must be applied, namely the principle of transparency, the principle of accountability, the principle of responsibility, the principle of independence, and the principle of fairness.